Indonesia - RAMLAH Wijaya; Masdar Mas'ud; Saripuddin D (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2021)
The study aims to determine and analyze the effect of individual ability, supervision and working conditions partially and simultaneously on job satisfaction of employees at the Civil Service Police Unit of Pangkep Regency, as well as the most dominant variable influencing employee job satisfaction at the Civil Service Police Unit of Pangkep Regency. The research approach is a survey approach. The research was conducted at the Civil Service Police Unit of Pangkep Regency. The research time was October to November 2019. This study used a survey method. The population in this study were all employees of the Pangkep District Civil Service Police Unit, as many as 40 people. Sampling in this study using a saturated sampling technique (census) in which all the population in this study were sampled. The sample used in this study were 47 people. The data analysis used was (Multiple Regression Analysis). The results showed that there was a positive and significant influence on individual ability, supervision and working conditions partially and simultaneously on job satisfaction of the employees of the Civil Service Police Unit of Pangkep Regency, as well as the individual ability variables that had the most dominant influence on employee job satisfaction at the Civil Service Police Unit of Pangkep Regency.